Fibroblast Growth Factor-23 and Chronic Allograft Injury in Pediatric Renal Transplant Recipients: a Midwest Pediatric Nephrology Consortium Study - Seifert, Michael E. (Pediatr Transplant, 2016)
BACKGROUND: The chronic kidney disease-mineral bone disorder (CKD-MBD) produces fibroblast growth factor-23 (FGF23) and related circulating pathogenic factors that are strongly associated with vascular injury and declining kidney function in native CKD. Similarly, chronic renal allograft injury (CRAI) is characterized by vascular injury and declining allograft function in transplant CKD. We hypothesized that circulating CKD-MBD factors could serve as non-invasive biomarkers of CRAI. METHODS: We conducted a cross-sectional, multicenter, case-control study. Cases (n=31) had transplant function > 20 mL/min/1.73 m(2) and biopsy-proven CRAI. Controls (n=31) had transplant function > 90 mL/min/1.73 m(2) and/or a biopsy with no detectable abnormality in the previous 6 months. We measured plasma CKD-MBD factors at a single time point using ELISA. RESULTS: Median (range) FGF23 levels were over 2-fold higher in CRAI versus controls [106 (10-475) pg/mL versus 45 (8-91) pg/mL; P<0.001]. FGF23 levels were inversely correlated with transplant function (r(2) = −0.617, P<0.001). Higher FGF23 levels were associated with increased odds of biopsy-proven CRAI after adjusting for transplant function, clinical, and demographic factors [OR (95% CI) 1.43 (1.23, 1.67)]. Relationships between additional CKD-MBD factors and CRAI were attenuated in multivariable models. CONCLUSIONS: Higher FGF23 levels were independently associated with biopsy-proven CRAI in children.